Pengelolaan Sampah Rumah Tangga Berkelanjutan Bernilai Ekonomi Berbasis Gender Equality and Social Inclusion di Kota Sukabumi - Bahroin Idris Tampubolon; Ujang Sehabudin; Adi Hadianto; Hendri Wijaya (Institut Pertanian Bogor, 2023)
The amount of waste in Sukabumi City tends to increase while the management rate is relatively low. Unmanaged waste generation is a problem of environmental degradation. Activities that can improve waste management, such as household waste from the source, are needed. This activity aims to provide knowledge to the community about the role of households in the waste management system and measure the level of change in knowledge of household members in the waste management stage from the source. The analysis method uses descriptive qualitative and quantitative. The methods of implementing the activity were lectures, focus group discussions, and interviews with respondents of the farmer women's group. The analysis tools used were pretest, posttest, and gap analysis. The activity results showed that households have a vital role and a significant contribution in managing household waste. The level of knowledge of farm women group participants has increased with a pretty good average value regarding the management of similar household waste.